Hak Restitusi bagi Korban Perdagangan Orang: Sebuah Langkah Penting Menuju Keadilan di Indonesia - Khairul Riza (Penerbit Goodwood, 2023)
Purpose: The purpose of this study was to determine the implementation of restitution rights for trafficking victims in Indonesia, the obstacles and challenges faced in the process of providing restitution for trafficking victims in Indonesia, and how it impacts the victim recovery process. Methodology: The method used is Empirical juridical research was conducted through a series of field interviews with respondents and informants. It also uses normative research, namely research through literature studies. Result: The results showed that in the context of granting restitution rights to trafficking victims in Indonesia, despite the supporting legal foundation, implementation on the ground has not fully reflected the values of justice espoused in Pancasila, especially in the precepts of